If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(3x + 2) + -6 = 0 Reorder the terms: 8(2 + 3x) + -6 = 0 (2 * 8 + 3x * 8) + -6 = 0 (16 + 24x) + -6 = 0 Reorder the terms: 16 + -6 + 24x = 0 Combine like terms: 16 + -6 = 10 10 + 24x = 0 Solving 10 + 24x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 24x = 0 + -10 Combine like terms: 10 + -10 = 0 0 + 24x = 0 + -10 24x = 0 + -10 Combine like terms: 0 + -10 = -10 24x = -10 Divide each side by '24'. x = -0.4166666667 Simplifying x = -0.4166666667
| 7(3g-3)=-37+5g | | -13k=-5k+48 | | 7(7-x)=2 | | 8x+c=k | | 4.8x=11.52 | | 5(x+1)-(2x-3)=3 | | 2.4/6=n/21 | | 5(2z-4)=-15-7z | | 20-3y/5=y-12 | | 4x^3+4x= | | -15=5u+5 | | 2.01=logx | | 8/6=28/m | | -2(2b+5)= | | 16x^2-9x+2=0 | | X+40=37 | | 6-12X=4+6x | | -7p+6=116+3p | | 5v-3=-18 | | 5/9(d-12)=10 | | 0=0.75*(-2)+0.25*(6*X-2*(1-X)-2) | | 2(37-8y)+3y=9 | | X^2+24=5x | | 2x(X-1)-4=12 | | 0.6x+8.2=7.3 | | 63/n=7 | | 7(3n-2)=24+9n | | -21=3x-6 | | 6(x-3)=-40 | | 49=2w+17 | | f(3x^4)=x^2/2 | | 48=-4x+20 |